Ահաբեկչության փոփոխվող բնույթը և Հնդկաստանի Հանրապետության հակաահաբեկչական քաղաքականությունը - Իսրայելյան, Արման («Զանգակ - 97»)
The terrorism is gradually changing in nature and Lhat has became morc obvious after the end of Cold War and collapse of lhe Soviel Union. The radical leftist groups rcsorting to terrorism arc giving way to well-organized and well financed transnational rcligious terrorist groups. The Overall increase during the past 15 years of terrorism motivated by a religious imperative reflects the convergence of new adversaries, motivations and tactics affecting terrorist patterns today. Internationa! terrorism's general tendency toward increasing lethality is also reflected in the percentage of internationa! terrorist incidents that result in one or more fatalities. The terrorist attacks on 9/11 in USA were the most deadly examples of this trend.
Keywords: Պատմություն; Ահաբեկչությունը Հնդկաստանում